Kisspeptin-10 elicits triphasic cytosolic calcium responses in immortalized GT1-7 GnRH neurones - Ozcan, Mete; Alcin, Ergul; Ayar, Ahmet; Yilmaz, Bayram; Sandal, Suleyman; Kelestimur, Haluk (Elsevier Ireland Ltd, 2011)
Kisspeptins, which are alternatively called as metastin since they were originally identified as products of metastasis suppressor gene KiSS-1, are the natural ligands for the G protein-coupled receptor 54 (GPR54). Kisspeptins are the most potent activators of hypothalamic-pituitary-gonadal (HPG) axis reported to date. The pulsatile pattern of GnRH release, which results in the intermittent release of gonadotropic hormones from the pituitary, has a critical importance for reproductive function but the factors responsible from this release pattern are not known. Therefore, the pattern of kisspeptin-induced intracellular signaling and the role of PKC in the intracellular signaling cascade were investigated by fluorescence calcium imaging using the immortalized GnRH-secreting GT1-7 hypothalamic neurons. Kisspeptin-10 caused a triphasic change characterized by an initial small increase followed by a significant decrease and increase in intracellular free calcium concentrations ([Ca2+](i)). The changes in [Ca2+](i) were significantly attenuated by pre-treatment with protein kinase C inhibitor. The compatibility of appeared mirrored-patterns of kisspeptin-10-induced changes in [Ca2+](i) concentrations in these neurons and GnRH secretion confirm the importance of intracellular calcium flux downstream from GPR54 through PKC signaling pathway. (C) 2011 Elsevier Ireland Ltd. All rights reserved.
Keywords: Kisspeptin-10; Calcium signaling; GT1-7 cells